Towards Generating Ambisonics Using Audio-Visual Cue for Virtual Reality - Smolic, Aljosa; Rana, Aakanksha; Oczinar, Cagri (My University, 2019)
Ambisonics i.e., a full-sphere surround sound, is quintessential with 360◦ visual content to provide a realistic virtual reality (VR) experience. While 360◦ visual content capture gained a tremendous boost recently, the estimation of corresponding spatial sound is still challenging due to the required sound-field microphones or information about the sound-source locations. In this paper, we introduce a novel problem of generating Ambisonics in 360◦ videos using the audiovisual cue. With this aim, firstly, a novel 360◦ audio-visual video dataset of 265 videos is introduced with annotated sound-source locations. Secondly, a pipeline is designed for an automatic Ambisonic estimation problem. Benefiting from the deep learning based audiovisual feature-embedding and prediction modules, our pipeline estimates the 3D sound-source locations and further use such locations to encode to the B-format. To benchmark our dataset and pipeline, we additionally propose evaluation criteria to investigate the performance using different 360◦ input representations. Our results demonstrate the efficacy of the proposed pipeline and open up a new area of research in 360◦ audio-visual analysis for future investigations.
ICASSP, IEEE International Conference on Acoustics, Speech and Signal Processing - Proceedings
44th International Conference on Acoustics, Speech, and Signal Processing, (ICASSP), Forthcoming.
PUBLISHED
Keywords: Virtual reality; 360 video; Spatial sound; Ambisonics; Multi-model; Deep learning; Creative Technologies; Multimedia & Creativity